Brexit and the UN Security Council: declining British influence?. (1st November 2019) - Gifkins, Jess; Jarvis, Samuel; Ralph, Jason
Abstract: The United Kingdom's decision to leave the European Union has ramifications beyond the UK and the EU. This article analyses the impact of the Brexit referendum on the UK's political capital in the United Nations Security Council; a dimension of Brexit that has received little attention thus far. Drawing on extensive elite interviews we show that the UK has considerable political capital in the Council, where it is seen as one of the most effective actors, but the reputational costs of Brexit are tarnishing this image. With case-studies on the UK's role in Somalia and Yemen we show how the UK has been able to further its interests with dual roles in the EU and Security Council, and the risks posed by tensions between trade and human rights after Brexit. We also analyse what it takes to be influential within the Security Council and argue that more attention should be paid to the practices of diplomacy. Influence is gained via penholding, strong diplomatic skill and a well-regarded UN permanent representative. The UK accrues political capital as a leader on the humanitarian and human rights side of the Council's agenda, but this reputation is at risk as it exits the EU.